Identification and Characterization of Sterol Acyltransferases Responsible for Steryl Ester Biosynthesis in Tomato - Lara, Juan A.; Burciaga-Monge, Alma; Chávez, Angel; Revés, Marc; Lavilla, Rodolfo; Arró, Monserrat; Boronat, Albert; Altabella, Teresa; Ferrer, Albert (Frontiers in Plant Science, 2018)
Esteryl esters (SE) serve as a storage pool of sterols that helps to maintain proper levels of free sterols (FS) in cell membranes throughout plant growth and development, and participates in the recycling of FS and fatty acids released from cell membranes in aging tissues. SE are synthesized by sterol acyltransferases, a family of enzymes that catalyze the transfer of fatty acil groups to the hydroxyl group at C-3 position of the sterol backbone. Sterol acyltransferases are categorized into acyl-CoA:sterol acyltransferases (ASAT) and phospholipid:sterol acyltransferases (PSAT) depending on whether the fatty acyl donor substrate is a long-chain acyl-CoA or a phospolipid. Until now, only Arabidopsis ASAT and PSAT enzymes (AtASAT1 and AtPSAT1) have been cloned and characterized in plants. Here we report the identification, cloning and functional characterization of the tomato (Solanum lycopersicum cv, Micro-Tom) orthologues. SlPSAT1 and SlASAT1 were able to restore SE to wild type levels in the Arabidopsis psat1-2 and asat1-1 knock-out mutants, respectively. Expression of SlPSAT1 in the psat1-2 background also prevented the toxicity caused by an external supply of mevalonate and the early senescence phenotype observed in detached leaves of this mutant, whereas expression of SlASAT1 in the asat1-1 mutant revealed a clear substrate preference of the tomato enzyme for the sterol precursors cycloartenol and 24-methylene cycloartanol. Subcellular localization studies using fluorescently tagged SlPSAT1 and SlASAT1 proteins revealed that SlPSAT1 localize in cytoplasmic lipid droplets (LD) while, in contrast to the endoplasmic reticulum (ER) localization of AtASAT1, SlASAT1 reside in the plasma membrane (PM). The possibility that PM-localized SlASAT1 may act catalytically in trans on their sterol substrates, which are presumably embedded in the ER membrane, is discussed. The widespread expression of SlPSAT1 and SlASAT1 genes in different tomato organs together with their moderate transcriptional response to several stresses suggests a dual role of SlPSAT1 and SlASAT1 in tomato plant and fruit development, and the adaptive responses to stress. Overall, this study contributes to enlarge the current knowledge on plant sterol acyltransferases and set the basis for further studies aimed at understanding the role of ES metabolism in tomato plant growth and development.